Enhancing critical thinking skills of EFL learners in Beninese secondary schools: Strategies and implementation - Koukpossi, Omolegbé Albert; Kottin, Assogba Evariste; Loko, Crépin D.; Koutchade, Innocent Sourou; Dossou, Mawumèvo Tchérak (Edelweiss Applied Science and Technology, 2024)
This paper investigates effective strategies for fostering critical thinking skills among English as a Foreign Language (EFL) learners in Beninese secondary schools. Critical thinking is essential for language and literacy development, as well as success in all domains. The importance of critical thinking in educational contexts is particularly crucial in a multicultural and diverse setting like Benin. This mixed-methods study combines qualitative interviews with EFL teachers and quantitative surveys with secondary school students to identify effective strategies. Results indicate that collaborative learning, inquiry-based instruction, problem-solving tasks, critical reading and writing exercises, and the integration of real-world issues into the curriculum are effective approaches. The study's findings suggest that incorporating these strategies into EFL instruction can significantly enhance the success of teaching and learning critical thinking in Beninese secondary schools.